HUBUNGAN ANTARA GAMBARAN HISTOPATOLOGI DENGAN JUMLAH LEUKOSIT PADA PENDERITA LIMFADENITIS TUBERKULOSIS DI NUSA TENGGARA BARAT TAHUN 2019 - Alfaridzi, Muhammad; Lestarini, Ima Arum; Djannah, Fathul (Faculty of Medicine Universitas Mataram, 2021)
Background: Indonesia is the 3rd country with the highest incidence of tuberculosis (TB) in the world. 15% of TB cases are EPTB with 50% of them being lymphadenitis TB (LNTB). The histopathological features of the biopsy samples play an important role in the diagnosis of this disease by producing the images of WOG or POG. The number of leukocytes can describe the immune response in people with LNTB. Methods: This study is an observational analytic study with a cross-sectional approach. The data were obtained by documenting the medical records of LNTB patients who were treated at the RSUD Provinsi NTB and RSUD Kota Mataram in the January 2019 - February 2020 period. Results: The total number of research subjects is 51 people. In the histopathological features, 37 samples included WOG, and 14 samples included POG. On the leukocyte count, none of the patients had leukopenia, 39 patients had normal leukocyte counts and 12 patients had leukocytosis. The results of the Spearman correlation test obtained p = 0.005 and r = 0.384 Conclusion: There is a significant correlation between the histopathological features and the number of leukocytes in patients with LNTB in NTB in January 2019 - February 2020. The correlation is weak.